Evaluation of Serum Alanine Aminotransferase Level in Areca Nut Chewers (Journal of Rangpur Medical College, 2025)
Background: Areca nut chewing is a common social tradition in many regions of the world particularly in Southeast Asia. It is one of the addictive substances that have toxic manifestations in immune, hepatic and other defense systems. Objective: To assess the effects of areca nut on liver function by serum alanine aminotransferase (ALT) level in areca nut chewers. Methods: This cross-sectional analytical study was conducted in department of Physiology, Rangpur Medical College, Rangpur from July 2022 to June 2023. Total number of 200, age range from 30 to 45 years, were selected after satisfactory inclusion and exclusion criteria. They were divided into two groups. Group A- 100 areca nut chewers, Group B-100 non areca nut chewers. Their liver function status was studied by measuring serum alanine aminotransferase level. For statistical analysis data were analyzed by students t-test, level of significance p